Spaces of Multilingualism - Blackwood, Robert; Røyneland, Unn (Routledge Critical Studies in Multilingualism, 2022)
This innovative collection explores critical issues in understanding multilingualism as a defining dimension of identity creation and negotiation in contemporary social life. Reinforcing interdisciplinary conversations on these themes, each chapter is co-authored by two different researchers, often those who have not written together before. The combined effect is a volume showcasing unique and dynamic perspectives on such topics as rethinking of language policy, testing of language rights, language pedagogy, meaning-making, and activism in the linguistic landscape. The book explores multilingualism through the lenses of spaces and policies as embodied in Elizabeth Lanza's body of work in the field, with a focus on the latest research on linguistic landscapes in diverse settings. Taken together, the book offers a window into better understanding issues around processes of change in and of languages and societies. This ground breaking volume will be of particular interest to students and scholars in multilingualism, applied linguistics, and sociolinguistics.